2023
DOI: 10.1007/s12928-022-00907-6
|View full text |Cite
|
Sign up to set email alerts
|

Complete revascularization in acute myocardial infarction: a clinical review

Abstract: In patients with ST segment elevation and non-ST elevation myocardial infarction (MI), multivessel (MV) coronary artery disease is found in approximately 50%, leading to worse clinical outcomes. Recent data have suggested that complete revascularization with MV percutaneous coronary intervention is associated with a reduced risk of major adverse cardiovascular events as compared to culprit vessel-only revascularization. However, the optimal timing of MV intervention, appropriate non-culprit lesion assessment, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 83 publications
1
6
0
1
Order By: Relevance
“…A review of 21 related randomized controlled trials (RCTs) suggests that complete revascularization can reduce the incidence of MACCEs in patients with acute myocardial infarction, [7] which was similar to our outcome of the Cox regression. It is suggested that for patients at high risk of ischemia with multiple vessel lesions, complete revascularization should be performed while fully evaluating the characteristics of the lesions.…”
supporting
confidence: 75%
“…A review of 21 related randomized controlled trials (RCTs) suggests that complete revascularization can reduce the incidence of MACCEs in patients with acute myocardial infarction, [7] which was similar to our outcome of the Cox regression. It is suggested that for patients at high risk of ischemia with multiple vessel lesions, complete revascularization should be performed while fully evaluating the characteristics of the lesions.…”
supporting
confidence: 75%
“…For instance, patients with AMI are likely to be older and have more comorbidities as shown in the present study, although they have an immediate therapeutic option such as primary percutaneous coronary intervention. 15 , 16 , 17 Differences in a diagnostic and therapeutic time frame may lead to different outcomes in patients with and without AMI. In this study, indeed, patients with AMI received the Impella earlier after hospital arrival than those without, suggesting that the devices were placed in an emergency situation in AMI than in non‐AMI.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 137 patients were screened for this study according to predefined inclusion and exclusion criteria. All the patients who presented with STEMI within 12 hours of the onset of symptoms were included in this study for primary PCI (Saito and Kobayashi, 2023). Similarly, patients with increased frequency of intracoronary thrombus on angiographic imaging were also included in this study.…”
Section: Methodsmentioning
confidence: 99%